The use of probiotics with antibiotics – how much do respondents from the territory of Novi Sad know about it - Kalić, Marina; Vojvodić, Sladjana; Katona, Gabor; Vidaković, Dušan (Archives of Pharmacy, 2022)
Human gastrointestinal tract microbiota offers many benefits to the human body through a number of physiological functions: strengthening the integrity of the gut, shaping the intestinal epithelium, collecting energy, protecting against pathogens and regulating host immunity. However, these mechanisms may be disrupted due to altered microbial composition. One of the reasons for this may be the use of antibiotics. The aim of this study was to determine the frequency of use of probiotic supplements during antibiotic therapy and knowledge of their proper use during and after antibiotic use. Quantitative non-experimental, descriptive design was used. The survey was distributed in pharmacies in Novi Sad. A total of 200 respondents were interviewed (50 male and 150 female). The results show that the largest percentage of respondents (53%) belong to the age category of 27-45 years. 72% stated that they used to use probiotics, and out of that number, 90% of them use probiotics during antibiotic therapy. Of those who use probiotics during antibiotic therapy, 85% use it properly, i.e. take a probiotic at least 2 hours before or after taking a dose of probiotics, while 15% take a probiotic at the same time as an antibiotic. When it comes to the length of probiotic use, 43% of respondents continue to use probiotics for at least 2 weeks after finishing antibiotic therapy, while 57% of respondents do not. The obtained results indicate the need for continuous education of the population, both on the potential benefits and on the proper use of probiotic-based supplements.